Characterization of drilling-related noise and curvelet-based evaluation of seismic-interferometric reflections for imaging of iron-bearing formations in Pilbara, Western Australia. Issue 1 (17th March 2021) - Chamarczuk, M; Malinowski, M; Draganov, D; Grant, A; Asgharzadeh, M; Urosevic, M
SUMMARY: Here we analyse ambient noise (AN) data generated during drilling of exploration boreholes and recorded using a dense array deployed over one of the numerous shallow iron-ore mineralization targets in the Pilbara region (Western Australia). Drilling and drilling-related operations were reoccurring in a sequence as described by the drillers' field notes, which created the rare opportunity to analyse AN data in time segments when only one type of technical process was predominantly active. Consequently, most of the recorded AN sources did not overlap in time and space. We extract the recordings in 15-min-long segments matching the time-span of single field-note entry and identify individually acting AN sources associated with specific field operations. The temporal variations of noise spectrograms and AN cross-correlations show dependency on the sequence of a few consecutive field operations and specific frequency–amplitude patterns associated with single field operations. These changes are directly reflected by the events visible in the retrieved virtual-source gathers (VSG), implying significant changes in noise temporal and spatial stationarity. Some VSGs represent the mixed contributions of surface and air waves. To remove the contributions of these arrivals to the reflection imaging, we visually inspect all data and select only field operations acting as stationary-phase sources specifically for the reflection retrieval. This was done for different receiver configurations inside PilbArray, and as a result, we obtain a collection of VSGs containing coherent body-wave reflections. Database of visually inspected VSGs is used to develop and benchmark a semi-automatic curvelet-based method for accurate parametrization of the reflection events retrieved from passive data and to compare the imaging quality of the different field operations. Common-midpoint stacks from manually and automatically selected VSGs show reflectivity consistent with the one obtained from the active-source data and related to the structure hosting shallow iron mineralization. Our results demonstrate the capacity of AN seismic interferometry to retrieve body-wave reflections and image shallow mineralization. They also provide an intermediate step toward automating the passive reflection imaging with similar data sets.